If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5 = 6x + -8 Reorder the terms: -5 + 3x = 6x + -8 Reorder the terms: -5 + 3x = -8 + 6x Solving -5 + 3x = -8 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -5 + 3x + -6x = -8 + 6x + -6x Combine like terms: 3x + -6x = -3x -5 + -3x = -8 + 6x + -6x Combine like terms: 6x + -6x = 0 -5 + -3x = -8 + 0 -5 + -3x = -8 Add '5' to each side of the equation. -5 + 5 + -3x = -8 + 5 Combine like terms: -5 + 5 = 0 0 + -3x = -8 + 5 -3x = -8 + 5 Combine like terms: -8 + 5 = -3 -3x = -3 Divide each side by '-3'. x = 1 Simplifying x = 1
| 7-3b=-5 | | -4b+9=53 | | 1-4b=-11 | | 3d-6=-12 | | -7w-6=-55 | | 3b-6=-9 | | n-13=34 | | Y-3=-3Y-43 | | 6m-7=23 | | -7n+5=-51 | | 4+3n=13 | | -4-7a=-4 | | 2-7x=-33 | | 7+4a=31 | | 8+3k=29 | | 14s^4-33s^2+18= | | 10+7b=-32 | | 2+4w=-38 | | -3d+8=20 | | 3-3n=-6 | | 3t+8=-7 | | 7d+1=-6 | | 8+5n=18 | | -6a+9=-45 | | -5m+1=-4 | | 7+4b=15 | | 5a-1=-51 | | 8-4b=-36 | | 3+6m=9 | | 9x+3=3(3x+1)-3 | | 5:x=0 | | 3x(2x+1x)= |